EFEKTIVITAS PENGEMBANGAN MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS KONSTRUKTIVISTIK PADA MATA KULIAH PENDIDIKAN KEWARGANEGRAAN - Evi Susilawati; Atmawarni Atmawarni; Liesna Andriany (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The purpose of this study is to see the effectiveness of developing constructive learning based learning models on subjects of Citizenship Education. Testing the effectiveness of this learning model is done by an experimental method by comparing the use of a blended learning model with a learning model that is usually done at the Education Faculty of the Islamic University of North Sumatra.This research  was carried out in the second semester (two) of the 2017/2018 school year with a population of 156 students and the sample was 56 students.The sampling technique in this study used cluster random sampling and selected a history education study program totaling 29 students and a Pancasila  and  Citizenship  Education  study  program  totaling  27  students. Hypothesis testing using independent T test. Based on the results of the T test obtained a significance value of 4.270 with a degree of freedom of 54. While the p-value for the two-sided test (test-tailed) is 0,000 which is smaller tha a = 0,05.The rejected  that the statistical hypothesis Ho :  mexperiment =  mcontrol. So  that  it  can  be  concluded  that  the  score  of  learning outcomes  in  the Citizenship Education course of the experimental group with different control groups.The conclusion of this study indicates that the results of the development of  a  constructive-based  blended  learning  model  in  Citizenship  Education courses are effective. Keywords: Blended Learning, Pendidikan Kewarganegaraan